Primary squamous cell carcinoma of the breast: A case report in a review of current literature - Ece Konuk; Erkan Arpaci; Selcuk Ergen; Emre Isik; Gamze Yurdakan (Journal of Oncological Sciences)
Primary squamous cell carcinoma of the breast is a rare malignancy considered a subtype of metaplastic breast carcinomas. Here we presented a case of 56-year-old female patient with a history of modified radical mastectomy, chemotherapy and radiotherapy for invasive ductal carcinoma of the right breast in 2005. After eleven years primary squamous cell carcinoma of the breast has been detected in the left breast. Any other localization were screened for squamous cell carcinoma but there was no localization beyond the breast. The case was discussed and complied in a review of current literature.